2016
DOI: 10.1128/genomea.01202-16
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Multiple-Protease-Producing Strain Geobacillus thermoleovorans N7 , a Thermophilic Bacterium Isolated from Paniphala Hot Spring, West Bengal, India

Abstract: Here, we present the draft genome sequence of Geobacillus thermoleovorans strain N7 (MCC 3175), isolated from Paniphala Hot Spring, West Bengal, India, which contains genes that encode several industrially and medically important thermostable enzymes like neutral protease, xylose isomerase, rhamnogalacturonan acetylesterase, nitrate and nitrite reductase, l-asparaginase, glutaminase, and RNase P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This difference may be explained by the potential stabilization of the enzyme with the used experimental set up such as buffer and their pH values. Besides, it was reported that the TPP is not only reflecting the temperature-dependent unfolding, but also an (Mohammadi et al, 2011) 99.66 65 60 QDY72590.1 Acetyl esterase GTNG_0744 (Bose et al, 2016) 90.08 60 59 irreversible thermal aggregation ( Jarzab et al, 2020;Seashore-Ludlow et al, 2020) and it may not be directly comparable with the biophysical methods. Collectively, it can be suggested that taking account of the plateau and R 2 values, the quality of the melting curve can give a useful prediction about the temperature at which the maximum enzyme activity would occur.…”
Section: T M Values Of Industrially Relevant Enzymesmentioning
confidence: 99%
“…This difference may be explained by the potential stabilization of the enzyme with the used experimental set up such as buffer and their pH values. Besides, it was reported that the TPP is not only reflecting the temperature-dependent unfolding, but also an (Mohammadi et al, 2011) 99.66 65 60 QDY72590.1 Acetyl esterase GTNG_0744 (Bose et al, 2016) 90.08 60 59 irreversible thermal aggregation ( Jarzab et al, 2020;Seashore-Ludlow et al, 2020) and it may not be directly comparable with the biophysical methods. Collectively, it can be suggested that taking account of the plateau and R 2 values, the quality of the melting curve can give a useful prediction about the temperature at which the maximum enzyme activity would occur.…”
Section: T M Values Of Industrially Relevant Enzymesmentioning
confidence: 99%